PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA SMP NEGERI 35 PALEMBANG - Ana Pertiwi; Jumroh Jumroh; Marhamah M. (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2020)
This study aims to determine whether or not there is a Contextual Learning Model (CTL) on the Communication Capabilities of Mathematics Students at 35 State Junior High Schools in Palembang. The population in this study were grade VII students of SMP Negeri 35 Palembang. Sampling in the study used Clauster Sampling and the selected class was Class VII.5, taken 30 people as the control class and Class VIII.3, up 30 people as the experimental class at SMP 35 Palembang. This research uses the True Experimental Desigh method in the form of Posttest Only Control Design. Data collection was carried out using the written test method in the form of an interesting essay on mathematical communication indicators, data analysis was performed with a statistical test t with a real level (∝) = 5%. Based on the results of the final analysis in this study, tcount = 2.729> ttable (0.05: 58) = 2.002 so that H0 is rejected, it can be concluded as a Contextual Teaching and Learning Model (CTL) Against the Mathematical Communication Capabilities of 35 State Junior High School Students in Palembang.